The Association of Pain Medication Usage and Quantitative Sensory Testing Outcomes in Fibromyalgia Patients: A Secondary Data Analysis - Luana Gola Alves; Kevin Pacheco-Barrios; Guilherme J. M. Lacerda; Felipe Fregni (NeuroSci)
Background: Fibromyalgia syndrome (FMS), a chronic pain syndrome affecting 0.2–6.6% of the general population, is known for its challenging diagnosis and treatment. The known dysregulation in the Endogenous Pain Modulatory System (EPMS) characteristic of the pathology contributes to enhanced pain sensitivity. Fibromyalgia patients, who are often overmedicated, may experience, in addition to the drug-related known adverse effects, effects on fibromyalgia sensory-related outcomes. Therefore, the focus of this analysis is to explore the bidirectional drug–sensory outcome interactions, indexed by the conditioned pain modulation (CPM), an important assessment element in regard to an EPMS’s efficacy. Methods: Baseline data from a randomized, double-blind, single-center (Boston-based tertiary hospital) clinical trial (NCT03371225) were analyzed. Participants aged 18–65 with an FMS diagnosis and resistance to common analgesics were included. Demographic, clinical, and sensory variables, including CPM, temporal summation, and Pain-60 outcomes, were collected alongside a pain medication diary. Multivariable regression models adjusted for confounders were applied to explore associations between medication classes and quantitative sensory outcomes. Results: Out of 101 recruited FMS patients, we categorized the use of the following medications: antidepressants with 50% use (n = 50), muscle relaxants with 26% use (n = 26), and gabapentin with 25% use (n = 25). The results showed that antidepressant use correlated with worsened CPM, Odds Ratio = 0.39 (95% CI = 0.17–0.91), while muscle relaxants were linked to increased TSPS, β coefficient = 0.72 (95% CI = 0.0021–1.4431). On the other hand, gabapentin use was associated with elevated Pain-60, OR = 2.68 (95% CI = 0.98–7.31). Interestingly, the use of low doses of opioids was not associated with altered sensory measures. Conclusion: This cross-sectional analysis suggests that common pain medications may affect quantitative sensory outcomes in FMS patients. We provided important insights into bidirectional drug–sensory outcome interactions and their influence on pain medicine.